2000
DOI: 10.1007/s002140000119
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculations with effective core potentials on trivalent lanthanide-terpyridine complexes

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The calculated M–N distances (Table 2) show that, in the gas phase, this higher affinity for Co II is also present: bond lengths are always longer for Cd II – than for Co II –pyridine systems, these differences being more marked for the less stable M II –py complexes (0.387 Å longer in Cd II –py than in Co II –py). It is noteworthy that the difference in M–N in bond lengths calculated with DFT in Cd II – and Co II –terpy complexes (0.334 Å) is slightly higher than that of the M–N ex bond (0.331 Å): this is in agreement with previous studies which found that small cations are able to better interact with the central nitrogen, due to the steric constraint of this rigid ligand 49…”
Section: Discussionsupporting
confidence: 91%
“…The calculated M–N distances (Table 2) show that, in the gas phase, this higher affinity for Co II is also present: bond lengths are always longer for Cd II – than for Co II –pyridine systems, these differences being more marked for the less stable M II –py complexes (0.387 Å longer in Cd II –py than in Co II –py). It is noteworthy that the difference in M–N in bond lengths calculated with DFT in Cd II – and Co II –terpy complexes (0.334 Å) is slightly higher than that of the M–N ex bond (0.331 Å): this is in agreement with previous studies which found that small cations are able to better interact with the central nitrogen, due to the steric constraint of this rigid ligand 49…”
Section: Discussionsupporting
confidence: 91%
“…The importance of relativistic effects in lanthanide complexes was examined by comparing the Ln-N bond distances in [Ln(tpy)] 3+ complexes calculated at the HF level with the large-core nonrelativistic [55] and quasirelativistic [47] pseudopotentials of Dolg et al The use of quasirelativistic pseudopotentials induced an increasing bond length contraction from La to Lu along the lanthanide series, as Lu exhibits larger relativistic effects than La [56].…”
Section: An Overview Of the Computational Methods For Treatment Of Lnmentioning
confidence: 99%
“…Additionally, the [51]. It is found that the calculated bond lengths are commonly longer than those measured in solid crystals, which is probably caused by the packing effects and the outer-sphere counterions in the complex crystals [37,58,59]. The Am-N bond lengths are comparable to those of Eu-N and the natural charges of Am(III) are mildly higher than those of Eu(III) in all the 1 : 2 complexes.…”
Section: Geometry and Nbo Analysismentioning
confidence: 66%